2022
DOI: 10.1007/s11904-022-00618-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outcomes and Risk Factors Among People Living with HIV

Abstract: Purpose of Review In this review, we examine the intersection of the HIV and COVID-19 epidemics with focus on COVID-19-related health outcomes and risk factors for SARS-CoV-2 among people living with HIV (PLWH). Recent Findings Evidence to date do not suggest a higher incidence of SARS-CoV-2 infection among PLWH compared to the general population, although—once exposed—PLWH are at greater risk of severe COVID-19 outcomes. Key risk factors for severe COVID-19 include non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 85 publications
2
48
0
3
Order By: Relevance
“…This study showed that risk factors of severe COVID-19 in PWH are non-HIV-related parameters, as previously reported in other countries [1,[4][5][6][7][8], although it is still controversial [4,5]. In the Italian cohort, the risk of poor COVID-19 outcome in PWH compared favorably with that observed in the HIV-negative COVID-19 patients of a similar mean age [6].…”
supporting
confidence: 83%
“…This study showed that risk factors of severe COVID-19 in PWH are non-HIV-related parameters, as previously reported in other countries [1,[4][5][6][7][8], although it is still controversial [4,5]. In the Italian cohort, the risk of poor COVID-19 outcome in PWH compared favorably with that observed in the HIV-negative COVID-19 patients of a similar mean age [6].…”
supporting
confidence: 83%
“…People living with HIV are a non-homogeneous group of immunocompromised persons, which includes both low CD4 count and ongoing immune activation impacting the response differently to and course of other viral infections [ 3 , 4 ]. Detectable viral load and concomitant chronic comorbidities independently increase the risk of severe outcomes of COVID-19 in this group of patients [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide an important foundation for strategies working to increase vaccine uptake in the future. PLWH are at a higher risk of developing SARS-CoV-2 complications [56]. A robust public health response to address vaccine hesitancy in this population is critical.…”
Section: Recommendations and Strategies For Future Vaccine Uptakementioning
confidence: 99%